Molecular Epidemiology of Human Papillomavirus Infection Among Chinese Women With Cervical Cytological Abnormalities - Wong, Eliza Lai-Yi; Cheung, Annie Wai-Ling; Chen, Zigui; Wong, Amy Yuen-Kwan; Yeung, Apple Chung-Man; Yau, Peter Sen-Yung; Chan, Paul Kay-Sheung (Frontiers in Public Health, 2022)
Background Virtually all invasive cervical cancers are caused by persistent genital human papillomavirus (HPV) infection. Therefore, HPV-based screening becomes an essential tool as one of the cervical prevention strategies to reduce the disease burden. Population-specific epidemiologic information on HPV infection among women with cytological abnormalities is essential to inform the strategy of HPV-based screening programme. The study also explored the presence of cutaneous HPV types (Beta-β and Gamma-γ) in cervical infections. Methods A cross-sectional study on Chinese women aged ≥25 years who were referred to public specialist out-patient clinics for colposcopy or further management of cervical cytological abnormalities were recruited between 2015 and 2016 in Hong Kong. HPV was detected and typified by the novel PCR-based Next-Generation Sequencing (NGS) strategies. Results The overall HPV infection rate was 74% and detected in 222 of the 300 respondents, with the prevalence of cutaneous HPV infection being 2.3%. The overall prevalence of HPV infection among women with current cytological abnormalities was 79.1% (197/249). The age-specific prevalence of HPV (any-type HPV infection) among women with cytological abnormalities reached the first peak with 87.9% in the age group of 35–39 years and gradually declined to 56.0% at 55–59 years. While a second peak occurred at 65 years or above (92.9%). HPV58 (13.7%), HPV52 (11.7%), HPV53 (11.2%), HPV16 (10.0%), HPV18 (5.2%), and HPV51 (5.2%) were the top five high-risk HPV genotypes among women with cytological abnormalities. Any-HPV type infection was significantly associated with an abnormal cervical smear (OR = 3.7; 95% CI 2.0–7.1), and high-risk HPV infection was also significantly associated with an abnormal cervical smear (OR = 6.3; 95% CI 3.0–13.5). Conclusion New evidence on the second peak of HPV infection at ≥65 years old suggests the necessity to review the current guideline for the cervical screening program extending to age 65 and above. Moreover, the high prevalence of two HPV genotypes—high-risk HPV51 and potential high-risk HPV53, among women with cytological abnormalities—suggests further research work is needed to confirm the contributory role of HPV51 and HPV53 in cervical cancer and the need for inclusion in the next generation of the HPV vaccine.